Fen bilgisi dersinde proje çalışmalarının öğrencilerin bilim anlayışına ve bilimsel süreçleri algılamalarına etkisi - Kınık, Ayşegül (My University, 2004)
THE EFFECT OF THE PROJECT WORKS OF SCIENCE LESSONS ON THE STUDENTS' UNDERSTANDING OF SCIENCE AND ON THEIR PERCEPTIONS OF SCIENTIFIC PROCESS The thought processes which are used in the scientific world are also valid for the arrangement of scientific education for children. The main target of primary school science lessons, is to provide a wide variety of experiences which establishes an approach that is based on research and exploration. These experiences use the main organizing principles, educationals targets and the scientific thought processes as the instruments of science. These processes are being used by the students for almost forty years, because of their validity in understanding the nature of science. The learning process for all students starts as a physical experience with the objects (Manual for Trainee Teacher). Do the project works of science lessons in primary school have an effect on the students' understanding of science and on their perception of scientific processes? is the problematic question of the research. The target of the research is to find out, if the project works of primary school science lessons have an effect on the students' understanding of science and on their perception of scientific processes. During the research the kids will be observed by doing projects and the necessary data will be assassed by qualitative data analysis processes. There will be commentary assesments based on the findings and observation forms that are taken from the research. There will be suggestions according to the results.
Keywords: Bilim; Eğitim; Fen Bilgisi_Öğrenim ve Öğretim; İlk öğretim; İlkokul konuları; sağlık; teknoloji